(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study evaluates the geotechnical characteristics of soils obtained from two landfill sites in Selangor, Malaysia, namely Tanjung Dua Belas and Air Hitam, to determine their suitability as compacted landfill liner materials. An integrated laboratory investigation was conducted to determine key physical properties, compaction behaviour under varying energy levels, consolidation characteristics, and stress-dependent hydraulic conductivity. The results reveal clear differences in engineering performance between the two soils. The Air Hitam soil achieved higher Maximum Dry Density (MDD) values ranging from 1.832 to 1.987 g/cm³ at lower Optimum Moisture Contents (OMC) between 11.92% and 14.81%, demonstrating more efficient particle packing and compaction response compared to the Tanjung Dua Belas soil, which recorded MDD values between 1.410 and 1.565 g/cm³ with higher OMC ranging from 18.56% to 22.56%. Consolidation analysis further indicated lower settlement for Air Hitam (1.401 mm) relative to Tanjung Dua Belas (1.583 mm), reflecting improved stiffness and reduced compressibility. Hydraulic conductivity decreased with increasing applied stress for both soils, with Air Hitam reducing from approximately 3.07 × 10⁻⁸ cm/s to 1.47 × 10⁻⁸ cm/s, while Tanjung Dua Belas decreased from 4.19 × 10⁻⁸ cm/s to 2.90 × 10⁻⁸ cm/s. The lower permeability and denser soil structure observed for Air Hitam indicate improved resistance to leachate migration under landfill loading conditions. Overall, the results demonstrate that soil physical characteristics strongly influence compaction, consolidation, and permeability behaviour, with the Air Hitam soil showing comparatively superior suitability for engineered landfill liner applications.